Energy Access: Pathway to Attaining Sustainable Development in Africa - Ogundipe, Adeyemi A.; Akinyemi, Opeyemi; Ogundipe, Oluwatomisin M. (International Journal of Energy Economics and Policy, 2018)
The study assesses the effect of energy use on social, economic and environmental sustainability in Africa. The energy sources considered in the study comprises four prominent sources in Africa, including: fossil fuel, solid fuel, electricity and natural gas consumption. The finding suggests that fossil fuel consumption and solid fuel constitute about 75 percent of energy use in the region and contributively worsen social and environmental conditions. The predominant consumption of these dirty energies has severely hampered child and adult survival and efficient delivery of services. Also, the time wasted in fetching biomass has constituted an impediment to learning capacities in children and women’s mobility. In the same manner, frequent exposure to fumes from the dirty energy sources had resulted in severe indoor air pollution and rising incidence of pneumonia, lung cancer and chronic obstructive pulmonary diseases in women and children. On the other hand, the empirical and conceptual analysis shows that access to clean and reliable energy sources (such as electricity) reduce time poverty, enhance gender empowerment and reduce environmental degradation. The study recommends structural policy reforms and transformation towards decentralizing energy provisions and adopting off-grid power solution to rural areas. Furthermore, African governments need to develop a sustainable energy financing mechanism through an affordable pricing template; this can be achieved by increasing local contents in energy provision and increasing the share of abundant domestic resource in energy mix. Keywords: Energy Access, Structural transformation, Sustainable Development, Africa JEL Classifications: Q43, K32, Q01 DOI: https://doi.org/10.32479/ijeep.7213